Factors associated with falls among the elderly attending a government clinic in Kuala Lumpur - Leong, Joyce Whye Sook; Mohd Zukri, Intan Nadia; Ching, Siew Mooi; Devaraj, Navin Kumar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Falls among the elderly can be associated with serious complications such as fractures, injuries and death. This study aims to ascertain the factors associated with falls among the elderly patients attending a government clinic located in Kuala Lumpur. Method: This was a cross-sectional study using a convenience sampling method. Data collection in 2017 from 322 elderly who attended the above clinic. A modified assisted self-administered questionnaire was used that contained the socio-demographic data, falls profile as well as extrinsic and intrinsic factors associated with falls. Analysis was done with SPSS v20.0. Results: 120 (37.27%) elderly reported falls in the past one year. The majority who had falls were females (n=76, 41.8%) and between the age of 80-89 years old (n=29, 44.6%). Malay ethnicity group, reported more falls compared to other ethnicities (n=93,44.5%). Significant associations were found between age, ethnicity and history of falls with falling (p<0.001). Intrinsic factors such as gait or imbalance problem, vision problem, using visual aids, having medical co-morbidities such as stroke, diabetes, Parkinson’s Dis-ease and osteoporosis, and being on antidiabetic drugs were also associated with increased risk of falling as well as extrinsic factors such as uneven floor, change in furniture position, poor lighting, lack of handrails, staircase, absence of railing at stairs and using walking aids (p<0.05). Conclusion: Factors founds to be associated with falls should be the primary intervention targets to help those who are at a heightened risk for falling such as visual problem and uneven floor, in order to reduce the negative impacts of falls.